2019
DOI: 10.1007/s10826-019-01604-4
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Quality of Life of Maltreated Children Who Have Been Reported to Advice and Reporting Centers On Child Abuse and Neglect

Abstract: Objectives To examine the self-reported quality of life of maltreated children, shortly after submission of a report to an advice and reporting center on child abuse and neglect, and the extent to which child and maltreatment characteristics were associated with quality of life. Methods Participants were 228 maltreated children aged 5-16 years (M = 9.99; SD = 3.20) and their primary caregiver. Children completed the Pediatric Quality of Life Inventory. One-sample t-tests were used to compare the self-reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…It is widely known that childhood adversities impact QoL; adolescents living in institutions have shown lower QoL than adolescents from the general population, which was attributed to their higher experiences of adversity (Greger et al, 2016 ). Childhood maltreatment and abuse have also been associated with lower QoL among both children and adult survivors (Affifi et al, 2007 ; Hoefnagels et al 2020 ; Weber et al, 2016 ). Empirical studies have shown that childhood IM predicts later adulthood physical, mental, and psychosocial problems (Carr et al, 2019 ; Carr et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely known that childhood adversities impact QoL; adolescents living in institutions have shown lower QoL than adolescents from the general population, which was attributed to their higher experiences of adversity (Greger et al, 2016 ). Childhood maltreatment and abuse have also been associated with lower QoL among both children and adult survivors (Affifi et al, 2007 ; Hoefnagels et al 2020 ; Weber et al, 2016 ). Empirical studies have shown that childhood IM predicts later adulthood physical, mental, and psychosocial problems (Carr et al, 2019 ; Carr et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Africa has been reported to have the highest rates of child neglect in the world where both boys and girls are being abused and neglected by their caregivers (Badoe, 2017;Hoefnagels et al, 2020;Sharley et al, 2019). The vice of child maltreatment is a major threat to the achievement of sustainable development goals on the continent and has become increasingly topical with a dramatic increase in recognition and an appreciation of the long-term harmful effects on the affected population (Badoe, 2017).…”
Section: Introductionmentioning
confidence: 99%